Acute retinal necrosis: A mini review - Hoogewoud, Florence; Rossi, Daniele C.; Stappler, Theodor; Guex-Crosier, Yan (Frontiers in Ophthalmology, 2022)
Acute retinal necrosis is a rare but potentially devastating disease. Even in the era of modern medicine, retinal detachment is a frequent complication leading to vison loss, as well as phthisis bulbi. Whereas IV acyclovir still remains the standard of care, high doses of valacyclovir with/without additional intravitreal injections of foscarnet have been used. In an attempt to reduce the retinal detachment rate, prophylactic laser treatment and early vitrectomy have been proposed. In this article, we aim to review current diagnostic and treatment modalities